Level-Based Classification of Electromagnetic Effects in Certification Tests of Electric Rolling Stock - Zubko, A. V. (Science and Transport Progress, 2025)
Purpose. To develop a conceptual framework for interpreting the results of electromagnetic compatibility (EMC) certification tests of electric rolling stock using a multi-level classification system. The study aims to establish a structured method for distinguishing different states of electromagnetic influence based on measured parameters of amplitude and duration, thereby improving the representation and understanding of test data within existing certification procedures. Methodology. Existing approaches to electromagnetic compatibility testing and data interpretation in railway applications were analyzed to identify limitations in differentiating levels of electromagnetic influence. A structured method for precise classification is proposed, based on normalized comparison of interference characteristics. The developed framework defines transition zones between safe and potentially critical operating conditions and allows flexible adaptation of threshold parameters depending on test conditions. This ensures compliance with certification requirements while enhancing the diagnostic depth and informativeness of the results. Findings. A multi-level classification system for electromagnetic interference has been developed, providing a comprehensive representation of EMC test results. The approach enables identification of transitional states and trends toward critical operating conditions that are not detectable under a dichotomous evaluation scheme. It allows a more accurate interpretation of test outcomes, supports early diagnostics of instability, and provides a quantitative basis for assessing the operational resilience of railway systems. Originality. A systematic, multi-level framework for interpreting EMC test results of electric rolling stock has been developed. Unlike conventional methods limited to threshold verification, the proposed approach accounts for the dynamics of parameter variations and their interdependencies, enabling predictive analysis and a more complete understanding of electromagnetic behavior under various operating conditions. Practical value. The developed methodology enhances the accuracy, transparency, and reliability of certification testing for electric locomotives, multiple-unit trains, and other electrically powered rolling stock. It contributes to safer and more efficient railway operation by providing engineers and certification authorities with a comprehensive analytical framework for assessing electromagnetic compatibility. The approach is applicable for optimizing design solutions, refining certification criteria, and supporting the modernization of railway infrastructure.